2017
DOI: 10.3390/ijms18122720
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Formulation Containing Nilvadipine Nanoparticles Prevents Retinal Dysfunction in Rats Injected with Streptozotocin

Abstract: Retinopathy leads to irreparable vision loss via capillary closure and areas of nonperfusion. However, the current instillation systems do not allow a sufficient amount of drug required to treat retinopathy to reach the posterior segment (retina); therefore, a new formulation targeting the posterior segment is expected as therapy for retinopathy. We prepared ophthalmic formulations containing nilvadipine nanoparticles (NILnano), and demonstrated whether the instillation of NILnano can prevent retinal dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…38 On the other hand, we previously found that nanoparticle formulations prepared by a bead mill method lead to an increase in BA, and the corneal toxicity of ophthalmic formulations containing nanoparticles is lower than that of traditional formulations (solution type). [13][14][15][16][17] In addition, we previously produced an ophthalmic formulation containing 0.5% indomethacin nanoparticles that showed high transcorneal penetration. 15 However, it is important to design ophthalmic formulations containing a higher content of drug nanoparticles in order to enhance the corneal penetration and duration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 On the other hand, we previously found that nanoparticle formulations prepared by a bead mill method lead to an increase in BA, and the corneal toxicity of ophthalmic formulations containing nanoparticles is lower than that of traditional formulations (solution type). [13][14][15][16][17] In addition, we previously produced an ophthalmic formulation containing 0.5% indomethacin nanoparticles that showed high transcorneal penetration. 15 However, it is important to design ophthalmic formulations containing a higher content of drug nanoparticles in order to enhance the corneal penetration and duration.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the corneal epithelium has a barrier function in the cornea, and we previously reported that particles ,200 nm in size can penetrate the corneal tissue. [13][14][15][16][17] Therefore, we demonstrated the corneal epithelial penetration of indomethacin nanoparticles using HCE-T cell monolayers. Moreover, it is known that incubation at cold temperature (4°C) inhibits all energy-dependent uptake in cells including endocytosis, 31 which is the major route by which nanomedicines are transported across membranes.…”
Section: ° ° ° °mentioning
confidence: 92%
See 1 more Smart Citation
“…Hematoxylin and eosin (HE) staining of the cornea in the normal and STZ rats was prepared as described previously [ 44 , 75 , 76 ]. The rats were anesthetized with sodium pentobarbital (30 mg/kg, i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Then, their eyes were removed and fixed in a SUPER FIX™ rapid fixative solution. Next, 3 µm paraffin sections were prepared and stained with H&E [37].…”
Section: Hematoxylin and Eosin (Hande) Staining Of The Lensmentioning
confidence: 99%